Kebijakan Fiskal pada Zaman Utsman Bin Affan dan Ali Bin Abi Thalib - Riyan Listianto Pasaribu; Putri Febiola; Riche Hendriko Putri; Faisal Hidayat (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the fiscal policies implemented during the leadership of Uthman bin Affan and Ali bin Abi Talib, two caliphs in Islamic history. The specific objectives of this research are: (1) to identify the main fiscal policies implemented by these two caliphs, (2) to analyze the impact of fiscal policies on the country's economy at that time, and (3) to explore the factors that influenced the selection of fiscal policies by the two caliphs. The research method used is a qualitative method with a literature study approach. Data is collected through a literature review of secondary data related to Islamic history, particularly during the leadership of Uthman bin Affan and Ali bin Abi Talib. Secondary data includes scientific journals, reference books, and other relevant sources. Data analysis is carried out using the content analysis method to identify and interpret the fiscal policies implemented by the two caliphs, as well as explore the factors that influenced the selection of these policies. The research findings are expected to provide a deeper understanding of fiscal policies in the early Islamic period and their implications for the country's economy at that time.